ANALISIS LIKUIDITAS PADA PADA PT. UNITAMA ADIUSAHA SHIPPING SAMARINDA - Wardani, Kusuma (EKONOMIA, 2013)
Issues to be addressed in this case is the ability of PT. Unitama Adiusaha Shipping Samarinda to meet short term obligations from 2009 to 2011.This study aims to determine the ability of PT. Unitama Adiusaha Shipping Samarinda in meeting liabilities (liquidity), cash turnover and to determine the effect on the company’s capital stock related to the company’s liquidity. Analysis tools used include Current Ratio, Quick Ratio, Cash Turnover, Cash Ratio and Inventory to Net Working Capital.Current Ratio in 2009 is 9,9 times, in 2010 is 5,7 times and in 2011 is 6 times. Conditions for the company in good condition considering the ratio in above the industry average. Quick Ratio in 2009 is 8,9 times, in 2010 is 5,5 times and in 2011 is 4,8 times. If the industry average for the quick ratio is 1,5 times state the company better than other companies even though the number ratio declaned each year. Cash Ratio in 2009 is 864%, in 2010 is 527% and in 2011 is 439%. State company has more than 2009 to 2011 average industry or in good condition due to the obligation to pay does not require a long time or do not need to sell some of the other current asets. Cash Turnover in 2009 is 73,34%, in 2010 is 59,57% and in 2011 is 73,93%. The state of the company in good condition because under the average for the industry. Inventory to Net Working Capital in 2009 is 8,73%, in 2010 is 4,89% an in 2011 is 24,97%. Unfavorable conditions of the company because the amount of inventory is still below standard liquidity ratios. In 2011 Inventory to Net Working Capital already above standard liquidity ratios but judging from the increase in the amount of the company in good shape because of the amount of inventories increased substantially.Based on the result of anaysis show that PT. Unitama Adiusaha Shipping Samarinda been able to meet its short term liabilities from year 2009 to 2011, so that the hypothesis can be accepted because of the liquidity ratio 5 analysis tools are used to test the feasibility of standard liquidity, four of them have been able to meet these standard’s. excessive amount of inventory which can put a heavy burden on the cash resources services company should improve the efficiency of operations to identify optimal inventory levels and thus can minimize the cost of the target in the stock.Password : PT. Unitama Adiusaha Shipping Samarinda been able to meet its short term liabilities assessed on several indicators.